Time Line Cell Tracking for the Approximation of Lagrangian Coherent Structures with Subgrid Accuracy. (5th December 2013) - Kuhn, A.; Engelke, W.; Rössl, C.; Hadwiger, M.; Theisel, H.
<x xml:space="preserve">Abstract</x> Lagrangian Coherent Structures (LCS) have become a widespread and powerful method to describe dynamic motion patterns in time‐dependent flow fields. The standard way to extract LCS is to compute height ridges in the Finite Time Lyapunov Exponent (FTLE) field. In this work, we present an alternative method to approximate Lagrangian features for 2D unsteady flow fields that achieves subgrid accuracy without additional particle sampling. We obtain this by a geometric reconstruction of the flow map using additional material constraints for the available samples. The illustration shows four approximations of LCS at different time steps in subgrid accuracy computed from a triangular grid containing 60 times 120 sample points for a heated cylinder simulation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>